Peritonectomy procedures and HIPEC in the treatment of peritoneal carcinomatosis from ovarian cancer: Long-term outcomes and perspectives from a high-volume center. Issue 2 (February 2016) - Muñoz-Casares, F.C.; Medina-Fernández, F.J.; Arjona-Sánchez, Á.; Casado-Adam, Á.; Sánchez-Hidalgo, J.M.; Rubio, M.J.; Ortega-Salas, R.; Muñoz-Villanueva, M.C.; Rufián-Peña, S.; Briceño, F.J.
Abstract: Background: Cytoreductive surgery with peritonectomy procedures and hyperthermic intraperitoneal chemotherapy (CRS + HIPEC) represents a radical therapeutic approach to achieve complete cytoreduction in ovarian peritoneal carcinomatosis. The aim of the present study was to analyze the outcomes obtained by the application of these procedures in a single center with extensive experience treating peritoneal carcinomatosis. Patients and methods: A series of 218 consecutive patients diagnosed with peritoneal carcinomatosis from primary or recurrent ovarian cancer (FIGO stage IIIC–IV) and treated with CRS + HIPEC between January 1996 and June 2012 were included in this observational study. Results: Peritoneal carcinomatosis was treated primarily in 56% (124/218) of the cases and recurrently in 43% (94/218). A total of 42/218 patients (19%) presented with FIGO stage IV. Compared to recurrent cases, patients with primary ovarian carcinomatosis were older and presented higher Peritoneal Cancer Index (PCI) and percentage of FIGO stage IV; however, no significant differences in survival (5-year overall survival in patients with R0 cytoreduction, 63% and 56%, respectively) were observed. Cytoreduction score, PCI, lymphatic involvement and surgical morbidity ≥Grade III were statistically significant prognostic factors for survival in both univariate and multivariate analysis. Conclusions: CRS + HIPEC treating macroscopic and microscopic disease is currently an excellent surgical approach to achieve high rates of complete cytoreduction and improve survival in patients with peritoneal carcinomatosis from ovarian cancer. In order to minimize the high potential morbidity of these procedures, CRS + HIPEC should be performed in highly experienced centers.